REMOVAL AND RETURN OF MAIN NUTRIENT ELEMENTS WITH BARLEY (HORDIUM VULGARE L.) PRODUCTS ON LIMED SOD-PODZOLIC SOIL OF WESTERN POLISSIA - Poliovyi, V. M.; Yashchenko, L. A.; Rovna, H. F.; Huk, B. V. (Scientific Progress & Innovations, 2021)
The nutrient elements’ removal is determined by the amount of their accumulation in the harvested part of the product. The aim of research was to determine the level of removal and return part of the main elements with spring barley straw in the soil, and the relative amount of removal per 1 ton of grain and straw. Different doses and types of lime materials (0.5–1.5 Ha of dolomite and 1.0 Ha of limestone), and recommended rate of fertilizers (N90P90K90) under spring barley with addition of sulfur S40 and microelements (ME) in the form of Nutrivant Plus grain micro-fertilizer were studied while conducting chemical reclamation of sod-podzolic soil. Liming and fertilizing had a positive effect on the grain and straw yield and changing the structure of barley plants. A wider ratio between grain and straw such as 1: 1.09 and 1: 1.04 in the variants of control and at application of N90P90K90 indicated the increased development of byproducts (straw). Decreasing grain: straw ratio to 0.83–0.96 on the limed variants affected the amount of nitrogen, phosphorus and potassium removal more than the dynamics of elements’ content depending on the yield of grain and straw. The higher NPK content in the dry matter was observed in variants with the addition of sulfur (S40) and Nutrivant Plus grain micro-fertilizer (2 kg/ha) in foliar application. Different levels of NPK removal were registered at changing the content of elements and yield of barley grain and straw. In grain, the highest amount of removal was noted for nitrogen (38.4–66.3 kg/ha) and phosphorus (18.1–31.7 kg/ha), while in straw potassium prevailed (36.5–45.8 kg/ha). Nutrients return with straw to the soil depended on fertilizing and liming and was at the level of 34.1–38.7 % for nitrogen, 19.2–30.9 % for phosphorus, 63.9–73.4 % for potassium of the total removal by plants. Thus, potassium return was by 2.0– 2.7 times higher than that of nitrogen and phosphorus. The removal by 1 ton of straw on average according to the results of the research (without control) was 8.5 kg/t of nitrogen, 2.5 kg/t of phosphorus and 11.0 kg/t of potassium. These indicators can be used for developing nutrition system of the next crop depending on byproduct amount and returning it at adding barley residues to the soil.